Application of Composite Nano-Bone Transplantation and Massage Exercise Rehabilitation Training in Patients Undergoing Limb Replantation - Yan Tang; Junxia Fu (Advances in Materials Science and Engineering)
With the great stride forward of socialist progress, various medical treatment measures have also made a leap forward in development, providing a deeper guarantee for people’s life safety. At the same time, the research field of nanotechnology has gradually developed in the medical field, which plays an important role in the development of medicine, and massage exercise rehabilitation training also provides convenience for patients’ recuperation. The purpose of this study is to study the application of composite NanoBone transplantation in patients with limb replantation and the application of massage exercise rehabilitation training in patients with limb replantation. The methods used in this paper are: consulting the literature to understand the composite NanoBone transplantation technology and massage exercise rehabilitation training methods, interviewing the patients and attending doctors, and asking about the selection method of experiment and questionnaire used in the paper, so as to carry out the questionnaire survey. The treatment group and the control group were set up to analyze the results. The results showed that there were no significant differences in T lymphocyte subsets, serum complement, and circulating immune complex in the replantation of amputated limbs. Combined with the clinical manifestations and pathological results, early rejection occurred, and the body temperature of the patients increased after clinical treatment; The characteristics of massage are not practical, the course of treatment is short, the effect is fast, the clinical operation is simple, easy to grasp, and has high clinical application and promotion value. The final test results showed that: comparing the two groups of patients before treatment, the VAS scores were 23% and 21%, respectively, and the treatment group scores were 23% and 21%, respectively. After treatment, the VAS scores of the test group and the control group were 29 % and 27%, respectively. The treatment group scored 2% higher than the control group. From this, it can be concluded that massage is better than traditional massage, and massage exercise has great application prospects in clinical practice.